Kajian Teologi Terhadap Hedonisme Dengan Ide Bunuh Diri Pada Remaja Dikaitkan Dengan Keadaan Orang Tua yang Tidak Mampu - Neneng Puspita Ayu (IAKN Tarutung, 2023)
Abstract:Attempted suicide is the last act of some people, including teenagers, when they are in severe turmoil. Who would have thought that hedonism is a new factor in relation to suicide attempts. Of course this is worrying news for parents, especially for those whose economy is below average. Based on this incident, the author tries to make a paper that is a theological study of hedonism with the idea of suicide in adolescents and its relation to the condition of parents who are unable or commonly called social inequality. With the reality that occurs the author uses qualitative methods, studies the middle of the disability of parents bibliography and collection of information regarding cases of suicide attempts strengthen the writing. As well as making the Bible the main basis in writing Through this writing, of course, the final hope is to complete understanding one of the readers is from the theological side regarding excessive lifestyles and their impact on adolescents, especially on the direction of suicidal thoughts in of the disability of parents. Keywords: theological studies, hedonism, adolescence, suicidal ideation Abstrak:Pencobaan bunuh diri menjadi tindakan terakhir beberapa orang termasuk remaja jika sedang berada pada kekalutan berat. Siapa yang menyangkah hedonisme menjadi salah satu faktor baru sekaitan dengan pencobaan bunuh diri. Tentu ini adalah berita mengkhawatirkan bagi para orang tua, terutama bagi mereka yang ekonominya di bawa rata-rata. Berdasarkan kejadian ini penulis mencoba membuat karya tulis yaitu penelitian kajian teologi terhadap hedonisme dengan ide bunuh diri pada remaja dan kaitannya dengan keadaan orang tua yang tidak mampu atau biasa disebut kesenjangan sosial. Dengan realitas yang terjadi penulis menggunakan metode kualitatif, studi pustaka serta pengumpulan informai mengenai kasus pencobaan bunuh diri memperkuat penulisan. Serta menjadikan Alkitab dasar utama dalam penulisan. Melalui penulisan ini tentu harapan akhirnya ialah memperlengkapi pemahaman pembaca salah satunya dari sisi teologi mengenai gaya hidup yang berlebihan dan dampaknya pada remaja khususnya pada pengarahan pikiran untuk bunuh diri di tengah ketidakmampuan orang tua.Kata kunci: kajian teologi, hedonisme, remaja, ide bunuh diri